Mobile Applications for Enhancing Oral Fluency in English as a Foreign Language Learners: A Systematic Review - Padilla Padilla, Karen; Valencia Silva, Estefanía; Anrango, Gladys Margarita; Flores Albuja, Fernando; Vásquez Flores, Steven (Revista Ecos de la Academia, 2025)
The increasing presence of Artificial Intelligence (AI) in education has significantly influenced how English as a Foreign Language (EFL) learners develop spoken proficiency. This systematic review explores the most recent mobile platforms designed to support speaking development, applying the PRISMA methodology to ensure an accurate and thorough literature selection. Academic works were extracted from databases including Scopus, Web of Science, Google Scholar, and SciELO. The review focused on three guiding inquiries: (1) What AI-based mobile apps are used by English teachers? (2) How do such apps contribute to independent speaking practice? (3) What constraints are associated with their classroom integration? The analysis indicated that mobile applications positively impact oral fluency through features like real-time correction, individualized practice routines, and improved learner autonomy. These tools enhance flexibility in language acquisition, allowing learners to manage their practice schedules and receive targeted support. Nonetheless, implementation challenges such as technological inequality and algorithmic limitations were identified. Future exploration should address these concerns to maximize the pedagogical potential of AI-enhanced mobile learning.
Keywords: AI-based feedback; EFL oral practice; learner autonomy; mobile-assisted language; speaking proficiency